Bioluminescent imaging and histopathologic characterization of WEEV neuroinvasion in outbred CD-1 mice. - Aaron T Phillips (Public Library of Science (PLoS), 2013)
Western equine encephalitis virus (WEEV; Alphavirus) is a mosquito-borne virus that can cause severe encephalitis in humans and equids. Previous studies have shown that intranasal infection of outbred CD-1 mice with the WEEV McMillan (McM) strain result in high mortality within 4 days of infection. Here in vivo and ex vivo bioluminescence (BLM) imaging was applied on mice intranasally infected with a recombinant McM virus expressing firefly luciferase (FLUC) to track viral neuroinvasion by FLUC detection and determine any correlation between BLM and viral titer. Immunological markers of disease (MCP-1 and IP-10) were measured and compared to wild type virus infection. Histopathology was guided by corresponding BLM images, and showed that neuroinvasion occurred primarily through cranial nerves, mainly in the olfactory tract. Olfactory bulb neurons were initially infected with subsequent spread of the infection into different regions of the brain. WEEV distribution was confirmed by immunohistochemistry as having marked neuronal infection but very few infected glial cells. Axons displayed infection patterns consistent with viral dissemination along the neuronal axis. The trigeminal nerve served as an additional route of neuroinvasion showing significant FLUC expression within the brainstem. The recombinant virus WEEV.McM.FLUC had attenuated replication kinetics and induced a weaker immunological response than WEEV.McM but produced comparable pathologies. Immunohistochemistry staining for FLUC and WEEV antigen showed that transgene expression was present in all areas of the CNS where virus was observed. BLM provides a quantifiable measure of alphaviral neural disease progression and a method for evaluating antiviral strategies.